Transientes, monoestabilidade e biestabilidade em processos de oxidação de eletrodos metálicos com formação de filmes : alguns casos simples - Brito, Gilberto Augusto de Oliveira (2005)
The simulation of simple models studied in this thesis showed that experimental current density/potential curves from processes of metal electrode oxidation with film formation can present peaks or discontinuities besides these curves can present the polarographic wave shape (sigmoidal shape). The experimental current density/potential curves wouldn t present hysteresis on quasi-stationary conditions. The peaks can be the result of measures made in non stationary conditions (transient conditions with measure times smaller than the relaxation time of the physical system under study) or conditions which looks like stationary conditions (transient conditons with measurement times bigger than the relaxation time of the physical system under study which could seem as stationary conditions) and the descontinuities would be the result of measures made in conditions which looks like stationary conditions. The experimental current density/potential curves presenting a peak or polarographic wave shape under conditions which looks like stationary conditions would point out that the physical system is in a monostability zone while those curves presenting discontinuities under conditions which looks like stationary conditions would point out that the physical system is in a bistability zone. Another important conclusion (obtained from the simulations) is that peaks and discontinuities in experimental current density/potential curves which are associated to the active/passive transition phenomenon can be the result of others phenomena. The stationary current density/potential curves simulated with the one adsorbed specie and constant dissolution model and the two adsorbed species and constant dissolution model, present the polarographic wave shape (this one due to these models are in a monostability zone) while the transient current density/potential curves present a peak. The stationary current density/potential curves simulated with the one adsorbed specie and oxide dissolution depending on coverage degree model and the two adsorbed species and oxide dissolution depending on coverage degree model can present the polarographic wave shape or a peak or hysteresis (hysteresis is due to these models are in a bistability zone) while the transient /E curves can present a peak or discontinuities (discontinuities are due to these models are in a bistability zone). Besides, the two adsorbed species and oxide dissolution depending on coverage degree model can present a kind of irreversibility when it is in a bistability zone.